Early Marriage and Various Factors That Affect - Sinta Pramitasari; Hario Megatsari (Universitas Airlangga, 2022)
Background: In the Sustainable Goal Development or SDGs, one of the efforts made is to achieve gender equality and empower women, namely SDGs goal number five. One of the efforts made is to eliminate child marriage and early age marriage. Objective: This study aims to identify the factors causing early age marriage in Wonosari sub-district, Gunungkidul district. The factors that influence early marriage are respondent characteristics, level of knowledge, attitudes, family support, the role of peers and access to information. Methods: This research is an analytical survey using a cross-sectional design with a quantitative approach. by using research subjects in the form of respondents as many as 115 respondents while the object of research is in Wonosari sub-district, Gunung Kidul Regency, Yogyakarta. Result: The results of the analysis in this study indicate that education has a negative and significant effect on early marriage. Knowledge has a negative and significant effect on early marriage. Family support has a positive and significant effect on early marriage. The role of peers has a positive and significant effect on early marriage. Access to information has a negative and significant effect on early marriage. Employment status has a negative and insignificant effect on early marriage. Family income has a negative and insignificant effect on early marriage and attitudes have a positive and insignificant effect on early marriage. Conclusion: Education, knowledge, the role of peers, access information have significant effect on early marriage. Employment status, family income, and attitudes have insignificant effect on early marriage.